Comparison of Agronomic Attributes Two Types of Panicum Grass on The Pot Trial - Tarsono, Tarsono (AgriSains, 2020)
A pot trial aimed comparing several aspects of agronomical atributes of two types of Panicum has been carried out from August to September 2018 in the greenhouse of Tadulako University, Palu. A completely randomized design (CRD) of two treatments which were repeated 10 times was used in this study. The variables observed included plant height, number of tillers, length of leaf-sheath, length of leaf-blade, leaf width, and dry matter production. The data collected was analyzed for variance using the SX program, with followed-up by the least significance difference test (P=0.05) for variables that were significantly affected by treatment. The results showed that Panicum sarmentosum grass has a similarity to Panicum maximum in terms of number of tillers, leaf-sheath length, leaf width, and plant height (P>0.05), except for leaf-blade length, and dry matter production (P<0.05).